Leiomyosarcoma of the maxilla - Zeynep Bayramoglu; Zeynep Gümrükçü (Wolters Kluwer Medknow Publications, 2018)
Leiomyosarcomas (LMSs) are relatively uncommon mesenchymal neoplasms of smooth muscle differentiation. Only 1% of the lesions occur in the head and neck region. Surgical excision with radiotherapy and chemotherapy is the most commonly executed procedure for recurrent and metastatic tumors. We report a rare LMS case of the maxilla, defined in a 19-year-old male patient. Following the diagnosis of a malignant neoplasm on frozen section, wide resection, with a 1 cm clear margin, was performed. The lesion was then sent for histopathological examination. Spindle cell malignancy was found in histopathological sections of the lesion, histologically consistent with LMS. A radiographical evaluation, magnetic resonance imaging, computerized tomography, and positron emission tomography were performed to detect metastasis. Signs of local recurrence or distant metastasis were not noted at the 12-month follow-up following the definitive surgical procedure.